CALLIGRAPHY LEARNING SYSTEM IN AR-RAUDLATUL HASANAH ISLAMIC BOARDING SCHOOL MEDAN, NORTH SUMATRA - Sekar Wulandari; Fahrurrozi Sihombing (Jurnal Eduslamic, 2023)
Calligraphy is a part of Islamic art related to writing. Because it is known as Islamic art, it is important to regenerate calligraphy to the Islamic generation. Calligraphy is usually subject that must be studied by students in Islamic education. However, the calligraphy learning system in each Islamic educational institution must be different. The purpose of this research is to find out the calligraphy learning system at Ar-Raudlatul Hasanah Islamic Boarding School in Medan, North Sumatra. This research is qualitative research with a field research approach and literature study. The data collection and analysis used interview techniques, where the researcher conducted interviews related to the discussion to several sources. The results showed that calligraphy learning at Ar-Raudlatul Hasanah Islamic Boarding School uses a system with the Ustadz or Ustadzah wrote examples of letters or sentences on the whiteboard, explained how to write and the rules. After that, the students practiced it directly in khat book provided by the pesantren.